2012
DOI: 10.1111/j.1471-0528.2012.03431.x
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of lymphadenectomy in uterine serous cancer

Abstract: Objective To estimate the survival impact of lymphadenectomy in women diagnosed with uterine serous cancer.Design Women with a diagnosis of uterine serous cancer were identified from the Surveillance, Epidemiology and End Results Program (SEER) from 1988 to 2007. Only surgically treated women were included.Setting The Surveillance, Epidemiology and End Results Program database provided data from 17 registries.Population The study population comprised 4178 women.Methods Statistical analyses using Student's t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…This survival advantage remained when patients with either grade 3 disease or deep myometrial invasion were treated with postoperative radiation therapy (P ¼ 0.0009) [17]. Mahdi et al performed a review of the Surveillance, Epidemiology, and End Results (SEER) data of 4178 women with serous endometrial cancer and found that any LND, as well as a more extensive LND, were associated with improved 5-year OS, even in patients with negative lymph nodes [18]. The SEPAL trial compared survival following surgical staging with pelvic nodal assessment versus pelvic and paraaortic nodal assessment in a retrospective fashion.…”
Section: Discussionmentioning
confidence: 99%
“…This survival advantage remained when patients with either grade 3 disease or deep myometrial invasion were treated with postoperative radiation therapy (P ¼ 0.0009) [17]. Mahdi et al performed a review of the Surveillance, Epidemiology, and End Results (SEER) data of 4178 women with serous endometrial cancer and found that any LND, as well as a more extensive LND, were associated with improved 5-year OS, even in patients with negative lymph nodes [18]. The SEPAL trial compared survival following surgical staging with pelvic nodal assessment versus pelvic and paraaortic nodal assessment in a retrospective fashion.…”
Section: Discussionmentioning
confidence: 99%
“…Patients Outcome [1] Women with uterine serous cancer surgically treated and with known lymphadenectomy status Overall survival [2] Women between the ages of 15 and 39 years with breast cancer Overall survival [3] Patients with radiographically determined noninvasive lung adenocarcinomas who underwent lobectomy and lymph node …”
Section: Refmentioning
confidence: 99%
“…When censoring occurs, the outcome 4 risk in censored subjects is assumed to be the same as those who remain in the cohort. [1] This 5 assumption is acceptable when subjects are censored because they reach the end of the study 6 follow-up period. However, the assumption that the likelihood of an outcome is the same in 7 patients who have a competing risk event is invalid.…”
mentioning
confidence: 99%
“…The rationale of lymph node dissection lies in prognostication, proper triage of patients for adjuvant therapy and, as suggested by cohort and registry-based studies, improved survival of patients with high-risk carcinoma [1][2][3].…”
Section: Introductionmentioning
confidence: 99%